Management of School Culture Change in Islamic Education and Its Impact on Madrasah Tsanawiyah Administrative Performance in Ciparay Bandung - Syam'iyah Syam'iyah; Moh Rifqi Salim Agil (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
An effective school is built upon the presence of well-performing human resources, including administrative employees who play a strategic role in the school's progress. School culture is one of the key factors influencing the performance of administrative employees. This study aims to determine the relationship between school culture change management and administrative performance among staff at Madrasah Tsanawiyah in Ciparay District, Bandung Regency. The research employs a quantitative approach, specifically a correlational method. Data was collected through questionnaire distribution. The data was then analyzed using various techniques, including instrument tests, partial indicator analysis, prerequisite tests (normality and linearity tests), correlation tests, and the coefficient of determination test. The results indicate that school culture change management is significantly correlated with administrative performance, with a significance value of 0.000 < 0.05. The correlation coefficient obtained is 0.770, which indicates a strong positive relationship, as it falls within the 0.61 - 0.80 category. Furthermore, the coefficient of determination (R-square) is 0.592, which means that 59.2% of the variation in administrative performance can be explained by the management of school culture change